Production of short-chain fatty acids (SCFAs) as chemicals or substrates for microbes to obtain biochemicals - Elia Tomás-Pejó; Cristina González-Fernández; Silvia Greses; Christian Kennes; Nuria Otero-Logilde; María C. Veiga; David Bolzonella; Bettina Müller; Volkmar Passoth (Biotechnology for Biofuels and Bioproducts, 2023)
Abstract Carboxylic acids have become interesting platform molecules in the last years due to their versatility to act as carbon sources for different microorganisms or as precursors for the chemical industry. Among carboxylic acids, short-chain fatty acids (SCFAs) such as acetic, propionic, butyric, valeric, and caproic acids can be biotechnologically produced in an anaerobic fermentation process from lignocellulose or other organic wastes of agricultural, industrial, or municipal origin. The biosynthesis of SCFAs is advantageous compared to chemical synthesis, since the latter relies on fossil-derived raw materials, expensive and toxic catalysts and harsh process conditions. This review article gives an overview on biosynthesis of SCFAs from complex waste products. Different applications of SCFAs are explored and how these acids can be considered as a source of bioproducts, aiming at the development of a circular economy. The use of SCFAs as platform molecules requires adequate concentration and separation processes that are also addressed in this review. Various microorganisms such as bacteria or oleaginous yeasts can efficiently use SCFA mixtures derived from anaerobic fermentation, an attribute that can be exploited in microbial electrolytic cells or to produce biopolymers such as microbial oils or polyhydroxyalkanoates. Promising technologies for the microbial conversion of SCFAs into bioproducts are outlined with recent examples, highlighting SCFAs as interesting platform molecules for the development of future bioeconomy.